2014
DOI: 10.1039/c4ta01469c
|View full text |Cite
|
Sign up to set email alerts
|

A hollow titanium oxynitride nanorod array as an electrode substrate prepared by the hot ammonia-induced Kirkendall effect

Abstract: The Kirkendall effect has been widely employed for the preparation of hollow nanostructures along with galvanic replacement and Ostwald ripening as a non-templating method. Despite many successful demonstrations for Kirkendall void formation, they have been mostly confined to the synthesis of hollow metal oxides and sulfides. In this work, we explored the feasibility of the Kirkendall effect for the preparation of a nitride compound in an effort to extend its peculiar merits, and discovered a new mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…The bottom line is NPs remain but with completely different morphologies . Note that previous reports indicate that nitridation of TiO 2 can lead to formation of TiON hollow particles in support of the current observations …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The bottom line is NPs remain but with completely different morphologies . Note that previous reports indicate that nitridation of TiO 2 can lead to formation of TiON hollow particles in support of the current observations …”
Section: Resultssupporting
confidence: 93%
“…Thus, transition metal, silica and boron based compounds are relatively easy to nitride/reduce using NH 3 at temperatures ca. 1000°C . In contrast, alumina nitrides easily only above 1100°C .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…19 The electrochemical deposition was performed under the same threeelectrode system employed for the PPy deposition in a 0.1 M Ni(NO3)2 solution heated to 65 o C.…”
Section: Electrodeposition Of Ni(oh)2 On N-cnc and Cfpmentioning
confidence: 99%
“…The Brunauer–Emmett–Teller (BET) surface areas of TiO 2 and TiO x N y were 8.7 and 27.4 m 2 g −1 , respectively, and the presence of mesopores/hollow voids in TiO x N y was also reflected in the pore size distribution (inset of Figure B). This observation revealed that porosity was introduced into TiO x N y during nitridation, which resulted from some of the oxygen vacancies created during nitridation merging into interior voids . To shed light on the local structural changes that occurred in bulk TiO 2 during nitridation, time‐resolved transmission electron microscopy (TEM) analysis was performed.…”
Section: Structural Parameters (Crystal Structure Lattice Parametersmentioning
confidence: 99%